Optimizing Local Tax Management for Achieving Regional Financial Independence - Hendra Hendra; Dadang Suwanda; Sampara Lukman; Meltarini Meltarini (PT. Global Research Collaboration, 2026)
This study examines the optimization of local tax management in achieving regional financial independence in Tulang Bawang Regency. A qualitative approach with a case study design was employed, drawing on data collected through interviews, observations, and document analysis. The findings reveal that local tax optimization reflects an ongoing structural transformation, characterized by the expansion of the tax base, strengthening of collection mechanisms, enhancement of supervision, administrative efficiency, and improved revenue planning. Initiatives such as system digitalization, database improvement, regulatory strengthening, and cross-institutional collaboration have contributed positively to local fiscal performance. However, the effectiveness of these efforts remains constrained by several systemic challenges, including limited data integration, inadequate analytical capacity of personnel, continued reliance on manual processes, and weak institutional coordination. These findings suggest that local tax optimization should not be viewed solely as a technical or administrative matter, but rather as a governance and institutional capacity issue. This study proposes a model of local tax management optimization that conceptualizes taxation as a layered and dynamic governance system. The model highlights the importance of transitioning toward system-driven taxation, strengthening data governance, and implementing risk-based compliance management to enhance the sustainability of regional financial independence.